ODPOWIEDZIALNOŚĆ ODSZKODOWAWCZA DUCHOWNEGO Z POWODU NARUSZENIA PRAWA PRZY ZAWIERANIU MAŁŻEŃSTWA - Smyczyński, Tadeusz (Wydział Prawa i Administracji UAM, 2002)
The author lists a clergyman’s possible transgressions that can occur when contracting a marriage, as well as the effects of such transgressions upon the couple contracting the marriage. Additionally, the author touches upon the issue of the liability for damages of the clergyman and those addressed by a claim for damages.Practice shows that the most common negligence o f clergymen when administering a marriage under the concordat terms is to exceed the 5-day deadline for submitting the documentation to the registry office. This time has been defined normatively as the final deadline and keeping it is therefore a prerequisite for the conclusion of any civil marriage before a clergyman. If, however, force majeure makes this deadline impossible to keep, then the clergyman should hand in the documents at a later date, mentioning the cause for the delay. This allows the head of the registry office to issue a marriage certificate. However, i f the clergyman fails to provide sufficient explanation for the delay, then the head of the registry office refuses to issue a marriage certificate and notifies the interested parties about this fact (art. 7 point 2 of Polish Civil Register Act). Only the Regional Court considering a motion or appeal from the decision can assess the provided explanation for the delay. A marriage before the head of registry office is contracted following the appropriate statements made by the couple (art. 7 § 4 of the Polish Family and Guardianship Code). In the view of this legal construction of a marriage, the requirement to draw up a certificate o f marriage when a marriage is contracted under the concordat terms, is in a certain way discordant. The strict character o f the five-day final deadline makes this discord even greater, as it further impedes the contraction of a marriage, even in the case of a minor delay. If the deadline served only the purpose of procedural order regulation, then the prerequisites to issue a certificate of marriage could be met more easily. In any way, also under the current regulations i f a certificate of marriage is issued despite a delay, then the prerequisites for the contraction of a marriage are met and the thus contracted religious marriage is recognized as valid under the Polish law.
CLERGYMAN’S LIABILITY FOR DAMAGES FOLLOWING A BREACH OF THE LAW WHEN CONTRACTING A MARRIAGE